Perkembangan Pemeriksaan Interferon-Gamma Release Assay (IGRA) dengan Metode T-SPOT.TB serta Aspek Klinis Pelaporan Hasil - Dewi, Juliani (MEDICINUS, 2020)
Latent tuberculosis infection (LTBI) screening and its treatment play important role in controlling tuberculosis (TB). Healthcare workers are known to be at high risk of latent TB infection. CDC suggests that every healthcare service should have TB controlling program. CDC recommends IGRA test for people who have history of contact with atypical mycobacteria patiens, screening in pregnancy, healthcare worker screening, and serial evaluation for Mycobacterium tuberculosis (MTB) infection. IGRA test kits that are commercially available are QFT and T-SPOT.TB. Term “indeterminate” is used as a borderline value in QFT, but in T-SPOT.TB, it means the result is invalid. Term "borderline zone" is used in T-SPOT.TB, but not in QFT. T-SPOT.TB uses borderline zone which is designed to reduce uncertainty result in narrow range around single cut-off point. There are still no recommendations to use IGRA test for therapeutic monitoring.